Acoustic and morphological differentiation in the frog Allobates femoralis: Relationships with the upper Madeira River and other potential geological barriers - Simões, Pedro Ivo (Biotropica, 2020)
We studied patterns of call acoustics and external morphological differentiation in populations of the dart-poison frog Allobates femoralis occurring in forested areas along a 250-km stretch of the upper Madeira River, Brazil. Multivariate analyses of variance using principal components representing shared acoustic and morphological parameters distinguished three groups in relation to call structure and external morphology: (1) populations belonging to a two-note call morphotype; (2) populations with four-note calls inhabiting the left riverbank; and (3) populations with four-note calls inhabiting the right riverbank. Our results report a case of Amazonian anuran diversity hidden by current taxonomy and provide evidence for the upper Madeira River being a boundary between distinct populations of A. femoralis, and suggest a new taxonomic interpretation for these groups. Samples that did not fit into the general differentiation pattern and the existence of a well-defined contact zone between two morphotypes on the left riverbank indicate that mechanisms complementary to river-barrier hypotheses are necessary to explain the phenotypic differentiation between populations. Our study shows that at least one anuran species shows congruence between population differentiation and separation by a large Amazonian river, as documented for birds and mammals. Conservation efforts should not consider the taxon now known as A. femoralis as a homogeneous entity. There is much within-taxon variability, which can be probably explained partly by the existence of cryptic species, partly by geological barriers and part of which currently has no obvious explanation. © 2008 The Author(s).